Leadless pacemaker implant in patients requiring CIED extraction: outcomes based upon timing of extraction. (14th October 2021) - Jung, W; Mondoly, P; Leclercq, C; Bordachar, P; Pasquie, J.L; Johansen, J.B; Zaidi, A; Keilegavlen, H; Mansourati, J; Nof, E; Theis, C; Roberts, P.R; et al.
Abstract: Background: Previous results from global Micra Transcatheter Pacemaker clinical trials have demonstrated leadless pacing as a safe and attractive option for patients with prior cardiac implantable electronic device (CIED) infection and extraction. Whether outcomes differ based upon the timing of prior device extraction has not been studied. Purpose: To describe characteristics and outcomes of patients undergoing CIED extraction during or prior to Micra implantation. Methods: Patients who underwent CIED explant and Micra implantation were identified from the Micra Post-Approval Registry and Micra Acute Performance studies. Baseline characteristics were summarized. A Fine-Gray competing risk model was used to compare risk for major complication through 24 months. Results: Of the 2739 patients included in the studies, 99 (3.6%) patients had CIED extraction the day of Micra implantation (same day) and 127 (4.6%) patients had CIED extraction within 30 days prior to Micra implantation (prior). Although infection was the primary reason for CIED extraction in both groups, a larger proportion of prior patients underwent extraction for this reason (87.4% vs. 42.4%). In contrast, more same day patients underwent CIED extraction for physician/elective reasons (16.2% vs. 3.1%). Same day patients prior device history included pacemaker (42 dual chamber and 30 single chamber), ICD (1 single chamber and 4 dual chamber), CRT (7 CRT-ICD and 13 CRT-P) while prior patients device history included pacemaker (29 single chamber, 80 dual chamber), ICD (3 dual chamber), CRT (5 CRT-ICD and 7 CRT-P). Overall, patients with extraction were aged 72.8±14.3 years, predominantly male (65.9%), and medical history was similar between groups, with the exception to CHF, which was higher for the same day group (18.2% vs 6.3%, P=0.021). The implant success rate was 98.0% for same day patients and 100% for prior patients. Median procedure duration was not significantly different between the groups (26.0 minutes and 25.0 minutes for same day and prior, respectively). Average follow-up duration was 16.5±13.8 months (range 0–53.4) for same day patients and 18.2±15.2 months (range 0–58.3) for subsequent patients. The rate of acute major complications (<30 days) was 5.1% for same day and 3.2% for prior. Through 24 months, the rate of major complications was 6.4% for same day and 6.0% for prior (HR: 1.19, 95% CI: 0.40 – 3.50, P=0.76, Figure). The rate of major complications related to infection was low and did not differ by group (1.01% vs. 1.57%, P=1.00) Conclusion: The Micra leadless pacemaker was implanted with a high success rate following CIED extraction. Outcomes following CIED extraction appear similar, whether the extraction is performed during or prior to Micra implant. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Medtronic, Inc.